Utilization of Project Design Model Using Communicative Learning Assisted by Educaplay Media in Learning to Writing Negotiation Texts on Class X Students - Nisrina Hana Suparwati; Dheni Harmaen; Yeni Cania Puspita (Journal of Practice Learning and Educational Development, 2025)
This study was conducted as an effort to improve negotiation text writing skills in grade X students in Indonesian language learning. This study used a descriptive quantitative method with a Quasi Experimental Design. The test data collection technique was in the form of pre-test and post-test. Based on the results of the study, there was an increase in students' writing skills, as seen from the average pre-test and post-test scores in the experimental class (64 to 89) and the control class (62 to 83). The effectiveness of the learning model was also strengthened by the results of the N-Gain test with results of 76.8640 for the experimental class (effective category) and 24.2203 for the control class (ineffective category). In addition, the independent sample t-test showed a significant difference between the learning outcomes of the experimental class and the control class with a significance value of 0.000 (< 0.05).